Effects of the concentration of Quercus infectoria galls (Manjakani) extract on moisture content and quality of its freeze-dried product - Pin, Kar Yong; Chuah, Teong Guan; A., Abdull Rashih; Mat Ali, Rasadah; Choong, Thomas Shean Yaw; Law, C. L. (Federation of Engineering Institutions of Islamic Countries, 2006)
Freeze-drying is a drying process based on sublimation under vacuum condition. This process minimizes the degradation of the heat-sensitive herbal product in order to preserve its bioactivity and medicinal properties. This work evaluates the effects of concentration of Quercus infectoria galls extract on the moisture content and quality of its freeze-dried product. Gall of Quercus infectoria, locally named as Manjakani, is a widely used traditional medicine originated from Western Asia and Southern Europe. The galls extract contains Tannic acids and Gallic acids, which are powerful astringents. The moisture content of the freeze-dried products were about 5 %w/w which were below the value required for product stability, 10 %w/w. From the results of High Performance Liquid Chromatography (HPLC) analysis, there was no significant variation between the chemical profiles of the products. Two sharp peaks were detected which indicated the presence of the bioactive compounds. Thus, the bioactivity of the Quercus infectoria galls extract was preserved. The concentration of chemical marker, gallic Acid, was calculated for each product. The energy for sublimation was also analyzed.